2020
DOI: 10.15252/emmm.201911739
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in GRK2 cause Jeune syndrome by impairing Hedgehog and canonical Wnt signaling

Abstract: Mutations in genes affecting primary cilia cause ciliopathies, a diverse group of disorders often affecting skeletal development. This includes Jeune syndrome or asphyxiating thoracic dystrophy (ATD), an autosomal recessive skeletal disorder. Unraveling the responsible molecular pathology helps illuminate mechanisms responsible for functional primary cilia. We identified two families with ATD caused by loss‐of‐function mutations in the gene encoding adrenergic receptor kinase 1 (ADRBK1 or GRK2). GRK2 cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 105 publications
(152 reference statements)
5
31
1
Order By: Relevance
“… 16 , 17 , 36 SAG, a derivative of chlorobenzothiophene, is a Hh pathway agonist 37 that activates Smo to activate Hh 19 in the presence of an intact primary cilium. 38 , 39 , 40 , 41 , 42 , 43 , 44 Although Hynes et al. 45 demonstrated that SAG promotes ciliogenesis in renal epithelial cells with defective cilia formation, whether ablation of Ihh affects ciliogenesis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 16 , 17 , 36 SAG, a derivative of chlorobenzothiophene, is a Hh pathway agonist 37 that activates Smo to activate Hh 19 in the presence of an intact primary cilium. 38 , 39 , 40 , 41 , 42 , 43 , 44 Although Hynes et al. 45 demonstrated that SAG promotes ciliogenesis in renal epithelial cells with defective cilia formation, whether ablation of Ihh affects ciliogenesis is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Using a standard microtome (RM2255, Leica), 6-μm sections were prepared and subsequently stained with Safranin O/fast green stain to visualize cartilage and assess proteoglycan content as described previously. 38 , 57 The slides were stained with Weigert’s iron hematoxylin and fast green and then stained with 0.1% Safranin O solution.…”
Section: Methodsmentioning
confidence: 99%
“…Besides adaptive dysregulation by pathophysiological conditions, gene mutations can also lead to altered expression levels. Mutations in GRK2 were detected in patients suffering from Jeune syndrome ( Bosakova et al, 2020 ). In one patient a mutation was identified to cause a functional loss of GRK2.…”
Section: Pathophysiological Effects Of Dysregulated Grk Expression Changesmentioning
confidence: 99%
“…Interestingly, this did not lead to expected embryonic lethality as seen in mice ( Jaber et al, 1996 ), as the patient was born alive, but passed away 5 days after birth. GRK2 was identified as an essential regulator of skeletogenesis ( Bosakova et al, 2020 ). The patient had a very small chest and suffered from pulmonary insufficiency, but did not show gross abnormalities in the central nervous system.…”
Section: Pathophysiological Effects Of Dysregulated Grk Expression Changesmentioning
confidence: 99%
“…We have previously characterized gene expression changes in the developing humerus under reduced mechanical stimulation ( Rolfe et al, 2014 ) and additionally showed that territories of Wnt and BMP signaling at the developing joint are disturbed under immobilization ( Rolfe et al, 2018 ; Singh et al, 2018 ). In this context it is intriguing that primary cilia potentially link mechanical and molecular signaling ( Elliott and Brugmann, 2019 ; Bosakova et al, 2020 ). Primary cilia loss has been shown to upregulate canonical Wnt signaling, in some contexts ( Corbit et al, 2008 ; Jiang et al, 2016 ; Patnaik et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%